Chloroplast Genome Sequences and Comparative Analyses of Combretaceae Mangroves with Related Species. (30th September 2020) - Zhang, Ying; Li, Hai-Li; Zhong, Jun-Di; Wang, Yun; Yuan, Chang-Chun
Abstract : In the Combretaceae family, only two species of Lumnitzera and one species of Laguncularia belong to mangroves. Among them, Lumnitzera littorea (Jack) Voigt. is an endangered mangrove plant in China for the limited occurrence and seed abortion. In contrast, Lumnitzera racemosa Willd. is known as the most widespread mangrove plant in China. Laguncularia racemosa C. F. Gaertn., an exotic mangrove in China, has the fast growth and high adaptation ability. To better understand the phylogenetic positions of these mangroves in Combretaceae and in Myrtales and to provide information for studies on evolutionary adaptation for intertidal habitat, the complete chloroplast (cp) genomes of Lu. racemosa and La. racemosa were sequenced. Furthermore, we present here the results from the assembly and annotation of the two cp genomes, which were further subjected to the comparative analysis with Lu. littorea cp genomes we published before and other eleven closely related species within Myrtales. The chloroplast genomes of the three Combretaceae mangrove species: Lu. littorea, Lu. racemosa, and La. racemosa are 159, 687 bp, 159, 473 bp, and 158, 311 bp in size. All three cp genomes host 130 genes including 85 protein-coding genes, 37 tRNAs, and 4 rRNAs. A comparative analysis of those three genomes revealed the high similarity of genes in coding-regions and conserved gene order in the IR and LSC/SSC regions. The differences between Lumnitzera and Laguncularia cp genomes are the locations of rps19 and rpl2 genes in the IR/SC boundary regions. Investigating the effects of selection events on shared protein-coding genes showed a relaxed selection had acted on the ycf2, ycf1, and matK genes of Combretaceae mangroves compared to the nonmangrove species Eucalyptus aromaphloia . The phylogenetic analysis based on the whole chloroplast genome sequence with one outgroup species strongly supported three Combretaceae mangroves together with other two Combretaceae species formed a cluster in Combretaceae. This study is the first report on the comparative analysis of three Combretaceae mangrove chloroplast genomes, which will provide the significant information for understanding photosynthesis and evolution in Combretaceae mangrove plants.